Charter and Ordinances of the City of Superior, at 390, Ordinance no. 286, § 18 (1896) - (:unkn) unknown (My University, 1896)
It shall be unlawful for any person, other than a policeman or other officer authorized to maintain the peace or to serve process, to carry or wear any pistol, sling-shot, knuckles, bowie knife, dirk, dagger or any other dangerous weapon within the limits of the City of Superior, and any person convicted of a violation of this section shall be punished by a fine of not less than ten (10) dollars nor more than one hundred (100) dollars.
Keywords: CARRY